Analysis of early diagnostic pathway for prostate cancer in Slovenia - Kokalj-Kokot, Mateja (Radiology and oncology (Ljubljana), 2024)
Background Prostate cancer (PCa) is a prevalent male malignancy globally. Prolonged diagnostic intervals are associated with poorer outcomes, emphasizing the need to optimize this process. This study aimed to evaluate the doctor and primary care interval, research their impact on patient survival and explore opportunities to improve PCa diagnostic pathway in primary care. Patients and methods A retrospective cohort study using cancer patients' anonymised primary care data and data of the Slovenian Cancer Registry. Results The study found that the doctor interval had a median duration of 0 days (interquartile range (IQR 0–6) and primary care interval a median duration of 5 days (IQR 0–58). Longer intervals were observed in patients with more than two comorbidities, where general practitioners didn't have access to laboratory diagnostic tests within their primary health care centre and when patients first presented with symptoms (reported symptoms at first presentation: dysuria, lower urinary tract symptoms LUTS, abdominal pain). The analysis also revealed a statistically significant association between lower 5-year survival rate and the accessibility of laboratory and ultrasound diagnostics in primary healthcare centres and a shorter 5-year survival of symptomatic patients in comparison to patients who were identified by elevated levels of prostate specific antigen (PSA). Conclusions This study shows that treating suspected PCa in primary care has a significant impact on 5-year survival. Several factors contribute to better survival, including easy access to laboratory and abdominal ultrasound in primary care centres. The study highlights the complex array of factors shaping PCa diagnosis, beyond individual clinicians' skills, encompassing test and service availability.
Keywords: interval doktorja; interval primarne zdravstvene oskrbe; rak prostate